EFSA statement on the requirements for whole genome sequence analysis of microorganisms intentionally used in the food chain - European Food Safety Authority (EFSA) (EFSA Journal, 2024)
Abstract Microorganisms, genetically modified or not, may be used in the food chain either as active agents, biomasses or as production organisms of substances of interest. The placement of such microorganisms or their derived substances/products in the European market may be subject to a premarket authorisation process. The authorisation process requires a risk assessment in order to establish the safety and/or the efficacy of the microorganism(s) when used in the food chain as such, as biomasses or as production strains. This includes a full molecular characterisation of the microorganism(s) under assessment. For certain regulated products, the use of whole genome sequence (WGS) data of the microorganism is established as a requirement for the risk assessment. In this regard, data obtained from WGS analysis can provide information on the unambiguous taxonomic identification of the strains, on the presence of genes of concern (e.g. those encoding virulence factors, resistance to antimicrobials of clinical relevance for humans and animals, production of harmful metabolites or of clinically relevant antimicrobials) and on the characterisation of genetic modification(s) (where relevant). This document provides recommendations to applicants on how to describe and report the results of WGS analyses in the context of an application for market authorisation of a regulated product. Indications are given on how to perform genome sequencing and the quality criteria/thresholds that should be reached, as well as the data and relevant information that need to be reported, if required. This updated document replaces the EFSA 2021 Statement and reflects the current knowledge in technologies and methodologies to be used to generate and analyse WGS data for the risk assessment of microorganisms.